Perkembangan Wilayah, Keselarasan Penggunaan Lahan Dengan Pola Ruang, Dan Arahan Rencana Pengembangan Wilayah Kabupaten Tangerang - Iis Rismawati; Santun R.P Sitorus; Darmawan Darmawan (TATALOKA, 2021)
Tangerang Regency has an economic structure dominated by the industrial sector. Population distribution, settlement location and industrial influenced land use patterns and regional development levels in Tangerang Regency. The objectives of this research are: to analyze the level of regional development and regional development inequality and factors that influence regional development; to analyze regional typology; to evaluate the consistency of land use with the Spatial Planning; and to formulate direction of the Tangerang Regency regional development plan. The method used are scalogram analysis, theil entrophy index analysis, cluster analysis, overlay and descriptive analysis. The results showed that the regional development level of the southern part of the region was higher than the northern part and the level of regional development inequality in the northern part of the region was higher than the southern part. Factors that influence the level of regional development are the percentage of settlement and industry areas, and the value of economic index, education index, and health index. Concerning typology of the area, in the northern part land use is dominated by agriculture, while in the southern region dominated by settlements and industries. The inconsistency of land use with spatial plan found mostly in the northern region. Thus, the first priority of regional development direction is to be located in the northern part that has a low level of regional development, high inequality value, high percentage of inconsistency of land use with spatial plan, and land use that is dominated by agriculture.